2020
DOI: 10.21203/rs.3.rs-27726/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

microRNAs Facilitate Comprehensive Responses of Bathymodiolinae Mussel Against Symbiotic and Nonsymbiotic Bacteria Stimulation

Abstract: Background:As the dominant species inhabiting both cold seeps and hydrothermal vents,Bathymodiolinae mussels are one of the most successful megafauna in the deep sea.They thrive in dark and food-insufficient environmentsby harboring sulfur-oxidizing bacteria (SOB)and/or methane-oxidizing bacteria (MOB)ingill bacteriocytesand obtain the majority of their nutrition from them.Many attempts have been made to decode the mechanisms underlying their symbiosis, which yetremained largely undisclosedfor years due to the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…Similar results for an activated immune response have been detected in previous analyses of deep‐sea mussels with depleted endosymbionts (Barros et al, 2015; Détrée et al, 2019). Moreover, differential expression of immune‐related genes was also detected in deep‐sea mussels under laboratory acclimation to bacterial challenges of symbiotic and environmental bacteria (Chen, Wang, Zhang, et al, 2021; Wang et al, 2019). Previous studies have revealed a concomitant immune response against symbiont depletion or bacterial invasion, highlighting the importance of immune‐related genes during these processes (Détrée et al, 2017; Wang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results for an activated immune response have been detected in previous analyses of deep‐sea mussels with depleted endosymbionts (Barros et al, 2015; Détrée et al, 2019). Moreover, differential expression of immune‐related genes was also detected in deep‐sea mussels under laboratory acclimation to bacterial challenges of symbiotic and environmental bacteria (Chen, Wang, Zhang, et al, 2021; Wang et al, 2019). Previous studies have revealed a concomitant immune response against symbiont depletion or bacterial invasion, highlighting the importance of immune‐related genes during these processes (Détrée et al, 2017; Wang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…For example, many critical immune‐related genes have been found to be expanded in the genome of deep‐sea mussels or positively selected in the deep‐sea lineage, revealing their importance in establishing symbiosis (Sun, Zhang, et al, 2017; Zheng et al, 2017). Several reports have demonstrated the participation of some pattern recognition receptors (PRRs), such as toll‐like receptors, C1q domain‐containing proteins, and lectins, in the innate response of Bathymodiolinae mussels to symbiotic and non‐symbiotic bacterial challenges (Chen, Wang, Zhang, et al, 2021; Martins et al, 2015; Wang et al, 2019). As for the nutritional interactions in symbiosis, current studies based on genomic or transcriptomic analysis have reported that various digestive enzymes and transporters might participate in intracellular transport and symbiont digestion and enable the transfer of nutrition from symbionts to the host (Ponnudurai et al, 2017; Zheng et al, 2017).…”
Section: Introductionmentioning
confidence: 99%